Inhibitory effect of Campomanesia xanthocarpa in platelet aggregation: Comparison and synergism with acetylsalicylic acid. Issue 154 (June 2017) - Otero, Juliana Soares; Hirsch, Gabriela Elisa; Klafke, Jonatas Zeni; Porto, Fernando Garcez; de Almeida, Amanda Spring; Nascimento, Sabrina; Schmidt, Aline; da Silva, Brenda; Pereira, Roberta Lelis Dias; Jaskulski, Mônica; Parisi, Mariana Migliorini; dos Santos Guarda, Naiara; et al.
Abstract: Background and aims: Cardiovascular diseases of thrombotic origin are related to high mortality and standard therapeutic agent used in this case is acetylsalicylic acid (ASA), but serious adverse events may occur. However, recent data has suggested the plant Campomanesia xanthocarpa has antiplatelet activity and could be a viable alternative. In this study we investigated the effects of the encapsulated powder of this plant in human platelet aggregation. Methods: 23 healthy subjects were randomly divided into three groups: (1) ASA (100 mg), (2) C. xanthocarpa (1000 mg) or (3) synergism (500 mg of C. xanthocarpa plush 50 mg of ASA); daily for five days. Antiplatelet activity was determined by turbidimetric method using ADP or arachidonic acid (AA) agonists before, 5 and 8 days after treatments. Results: Treatment with C. xanthocarpa and synergism caused a reduction of 8 ± 13.5% and 12.5 ± 5% in platelet aggregation induced by ADP after 5 days of treatment, respectively, returning to basal levels after 8 days. For AA agonist, 5 days of treatment with C. xanthocarpa, ASA or synergism caused a reduction of 46 ± 15%, 36 ± 12% and 69.3 ± 6% in platelet aggregation, respectively, and first two groups returned to baseline values 8 days after treatment ended. Synergism group prolonged antiplatelet effect maintaining aggregation reduction after 8 days the end of treatment. Conclusion: C. xanthocarpa showed antiplatelet action when stimulated by agonist AA, and contributed to the antiplatelet effect when associated with ASA for both agonists, allowing dose reduction to 50 mg. Highlights: C. xanthocarpa inhibits platelet aggregation induced by arachidonic acid. The association between ASA and C. xanthocarpa potentiates the inhibitory effect. C. xanthocarpa associated with aspirin prolonged antiplatelet effect.